Construction of Tasamuh Concept into Islamic Education Curriculum at Islamic College of Melbourne Australia - Suherman, Rudi; Bakhtiar, Moch.; Hariyanto, Bambang (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This article describes how the values of tasamuh (religious tolerance) are integrated into the Islamic private learning curriculum and manifested in the social life of the people in Australia. Islamic values are believed by both Muslim and non-Muslim communities to create social stability, amidst the phenomenon of Islamophobia and securalization in Australia. Not only integration, but Islamic values are realized in schools and social life so as to form a harmonious and anti-conflict life order. This research is qualitative with a phenomenological approach. Data were collected from interviews and documentation studies. The findings show that Islamic education in Australia has experienced rapid development since the time when the education curriculum internalized tasamuh in social life. The integration of the concept of tasamuh in the Islamic College of Melbourne Australia educational institution is in the form of the inclusion of the value of tasamuh (tolerance), ukhuwah (brotherhood) and ta’aruf (getting to know each other). These values are internalized in the curriculum, especially in the aspects of learning and output. Third, the construction of the concept of tasamuh at the Islamic College of Melbourne Australia is realized in the school and social environment through extracurricular activities, social care and national events.